Towards building equitable health systems in Sub-Saharan Africa: lessons from case studies on operational research - Theobald, Sally (BioMed Central, 2009)
BACKGROUND: Published practical examples of how to bridge gaps between research, policy and practice in health systems research in Sub Saharan Africa are scarce. The aim of our study was to use a case study approach to analyse how and why different operational health research projects in Africa have contributed to health systems strengthening and promoted equity in health service provision. METHODS: Using case studies we have collated and analysed practical examples of operational research projects on health in Sub-Saharan Africa which demonstrate how the links between research, policy and action can be strengthened to build effective and pro-poor health systems. To ensure rigour, we selected the case studies using pre-defined criteria, mapped their characteristics systematically using a case study development framework, and analysed the research impact process of each case study using the RAPID framework for research-policy links. This process enabled analysis of common themes, successes and weaknesses. RESULTS: 3 operational research projects met our case study criteria: HIV counselling and testing services in Kenya; provision of TB services in grocery stores in Malawi; and community diagnostics for anaemia, TB and malaria in Nigeria. Political context and external influences: in each case study context there was a need for new knowledge and approaches to meet policy requirements for equitable service delivery. Collaboration between researchers and key policy players began at the inception of operational research cycles. Links: critical in these operational research projects was the development of partnerships for capacity building to support new services or new players in service delivery. Evidence: evidence was used to promote policy dialogue around equity in different ways throughout the research cycle, such as in determining the topic area and in development of indicators. CONCLUSION: Building equitable health systems means considering equity at different stages of the research cycle. Partnerships for capacity building promotes demand, delivery and uptake of research. Links with those who use and benefit from research, such as communities, service providers and policy makers, contribute to the timeliness and relevance of the research agenda and a receptive research-policy-practice interface. Our study highlights the need to advocate for a global research culture that values and funds these multiple levels of engagement.